PLANNING FOR READING: ACTIVITIES FOR BEFORE, DURING AND AFTER READING - Juli Rachmadani Hasibuan (BAHAS, 2015)
Reading is an interactive process that goes on between the reader and the text, resulting in comprehension. The text presents letters, words, sentences, and paragraphs that encode meaning. The reader uses knowledge, skills, and strategies to determine what that meaning is. Good readers tend to use a range of strategies while reading such as making predictions before reading, making connections to personal experiences and knowledge, and engaging in self-monitoring (on-going checks of text comprehension). Teachers can model, teach, and promote the use of these and other effective comprehension strategies to help their students become even more proficient readers. The need for students to be actively is engaged in the reading process. Teachers can explain key strategies and model the types of actions students can take before, during, and after reading. Keywords: Reading, activities before, during and after reading